2016
DOI: 10.1002/btpr.2261
|View full text |Cite
|
Sign up to set email alerts
|

Selective cytotoxicity and modulation of apoptotic signature of breast cancer cells by Pithecellobium dulce leaf extracts

Abstract: We report the potent and selective cytotoxicity of the crude aqueous leaf extract from the medicinal plant, Pithecellobium dulce toward the human breast cancer cells (MCF-7), but not the normal cells (MCF-10A). The cytotoxicity was found to be dose and time dependent, as 300 µg/mL of the extract decreased the cell viability to 50% (IC50 ) in 48 h. The induction of apoptosis in the breast cancer cells after treatment was confirmed by significant percentage (24.7%), of early apoptotic cells (AnnexinV (+) Propidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In addition to normal cell testing, herbal components have also been found to inhibit cancer cells and have shown varying activities from toxic to safe. P. dulce bark and leaf lipophilic fractions were assessed for their cytotoxic activity using an MTT cell viability assay against two different cancer cell lines, namely, hepatocellular carcinoma and colon carcinoma cells, and the lipophilic extract was reported to possess significant cytotoxic activity in a colon carcinoma cancer line [ 40 ], and it was shown that there was cytotoxic potential of P. dulce leaf extracts on breast cancer cells (MCF-7 cell line) at 400 mg/mL [ 41 ]. In addition, a C. fistula methanol extract reduced prostate human cancer cell line viability in a dose-dependent manner in the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to normal cell testing, herbal components have also been found to inhibit cancer cells and have shown varying activities from toxic to safe. P. dulce bark and leaf lipophilic fractions were assessed for their cytotoxic activity using an MTT cell viability assay against two different cancer cell lines, namely, hepatocellular carcinoma and colon carcinoma cells, and the lipophilic extract was reported to possess significant cytotoxic activity in a colon carcinoma cancer line [ 40 ], and it was shown that there was cytotoxic potential of P. dulce leaf extracts on breast cancer cells (MCF-7 cell line) at 400 mg/mL [ 41 ]. In addition, a C. fistula methanol extract reduced prostate human cancer cell line viability in a dose-dependent manner in the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is very important to evaluate the plant extracts for discovering the compounds that may have a novelty to be drugs for treating the diseases. There are many extracts which record as having antibreast cancer effect that have been reported like Zingiber officinale [3], Morus lba L. [4], Angelica archangelica [5], Aralia elata [6], Pithecellobium dulce [7] Abelmoschus esculentus [8].…”
Section: Introductionmentioning
confidence: 99%
“…The herbal extracts, which are an excellent scavenger of free radicals, have been used to treat a variety of diseases. It contains a variety of phytochemicals that work together to combat diseases that are resistant to purified compounds (Sharma, 2016). Flavopiridol, Epipodophyllotoxin, Noscapine, Paclitaxel, Vindesine, Vinorelbine, Vinflunine, Pomiferin, Roscovitine, Sulphoraphane, Vincristine, and Vinblastin are few examples of well-known plant derived anticancer drugs (Greenwell and Rahman, 2015;Pereira et al, 2016, Basu andMaier, 2018).…”
Section: Introductionmentioning
confidence: 99%